The Ear, the Eye, and the Arm : a novel - Farmer, Nancy, 1941- (New York : Puffin Books, 1995)
In 2194 in Zimbabwe, General Matsika's three children are kidnapped and put to work in a plastic mine while three mutant detectives use their special powers to search for them.
Keywords: Black people -- Zimbabwe -- Fiction; Zimbabwe -- Fiction; Science fiction